The Effect of Addressing Attraction And Price Reduction on Consumer Purchase Interest In Alfalah Car Service Medan - Putri Syahrida Pratiwi; Tukimin Lubis (International Journal of Economics (IJEC), 2022)
This study aims to determine whether the attractiveness of advertising and price discounts have a positive and significant effect either partially or simultaneously on consumer buying interest at Alfalah mobil service Medan. This study uses a quantitative descriptive method with data analysis techniques used, namely multiple linear regression and hypothesis testing (t-test, F-test and coefficient of determination test). With a total population of 452 respondents with a tolerance limit of 10% which is calculated by the Slovin formula, the number of samples obtained is 82 respondents by determining the sample using random sampling technique. Meanwhile, the simultaneous test results show that the attractiveness of advertising (X1 ) and discounted prices (X2 ) has a positive effect on consumer buying interest at Alfalah Mobil Service Medan, it can be seen from the calculated F value (50.955) > F table ( 3.11) and a significant value of 0.000 <0.05. The value of the coefficient of determination reaches 0.563 , which means that the attractiveness of advertising and price discounts affects consumer buying interest at Alfalah Mobil Service Medan by 56.3%. While the remaining 43.7% is influenced by other factors outside of this study.